Stinginess, Generosity in The Qur’an, And Their Impact On Individuals and Society - Hawre Omar Awla; Shukur Eskander Salih (QALAAI ZANIST JOURNAL, 2020)
This study entitled "Stinginess, Generosity in the Qur’an, and their impact on Individuals and Society" Stinginess: it goes against Generosity and Goodness, refraining from acquiring supplies that should not be fully kept, and the Stinginess raises panic on properties in which it’s considered as a nasty deed in the holy Quran and Prophetic Hadiths. Generosity: is the ease of spending and avoiding purchasing non-essential supplies. Stinginess types go as follows: The most disgusting type is stinginess of money, as well as stinginess of greeting, food, stinginess of lack of words and praying on prophet (PBUH). Stinginess is a psychological illness that has a bad impact on anyone in society. Generosity: It is one of the highest morals of a Muslim. More significantly, avoid getting jealous of anyone’s property. Al the Quran verses that dispraised stinginess are sufficient to demonstrate this abhorrent habit, and stinginess influences individuals and society, whether it is by spoiling the relationships between people and depriving the reward of spending for God’s sake, weak faith in God can cause of the doubting in God, raising hatred towards people, and depriving himself of the permissible pleasures in this life. The remedy of the disease is patience and conviction, and considering the consequences of the misers in this world and the hereafter.